A Method of Improving Oral English Teaching Based on PLS-SEM. (11th May 2022) - Peng, Dongxiao
Abstract : To improve the quality of oral English teaching, we must first analyze the factors that affect teaching. Second, it examines the relationship between these factors in order to aid the teaching staff's oral English instruction and improve the learners' oral English pronunciation. As a result, determining how to analyze the relationship between various factors in the process of oral English teaching is a problem that is still being worked on. In response to this issue, this paper proposes a partial least squares-structural equation modeling (PLS-SEM) method for improving oral English teaching. The central idea of this method is to first analyze and summarize all relevant factors affecting oral English teaching as thoroughly as possible. Second, the influencing factors are quantified into specific numerical data, and the data are subjected to a series of preprocessing steps. Third, the PLS-SEM model is trained, and the preprocessed data are fed into the statistical analysis. Finally, the relationship between the factors is summarized based on the statistical analysis results. This paper evaluates the PLS-SEM model in terms of reliability and validity in order to validate the effectiveness of the method used. The PLS-SEM model developed in this paper for improving oral English teaching has high reliability, validity, and explanatory power. This method-based oral English teaching strategy can improve students' oral English levels and has a high practical application value.